Effective talent management practices for organisation in Malaysian SMEs - Cheaw, Wen Cheng (2020)
Talent management practices are currently a common strategic practice that is employed by large and multinational organisations due to its ability to attract and retain talents. The competition to attract and retain talents is a challenge faced worldwide because organisations want to gain significant advantages over their competitors and constant development of innovative products and solutions to their customers. Movement of talents are now more fluid and less constrained compared to previous decades as a result of technological advancement globally. Small and Medium Enterprises (SME) are also facing the same challenges but with increased difficulties due to their size and financial stamina against larger organisations. SMEs are the very backbone of every nation’s economic development and they contribute significantly towards a country’s GDP growth. The aim of this research is to examine the level of effectiveness of Talent Management practices for Organisations in Malaysian SME. The organisational performance becomes the key indicator of the effective practices of Talent Management. Talent management practices encompasses Recruitment, Training and Development, Rewards and Recognition and Retention. Primary data was collected from 116 respondents working in Malaysian SME through an online questionnaire. This study reveals that Talent Management practices are effective towards organisational performances. However, it also revealed that there is a gap in expectation between their current organisation Talent Management practices and effective Talent Management practices. Recommendations for SME owners were offered in the form of alliance with Universities and Vocational schools, providing avenues for talents to gain professional certifications, offering variety of benefits through cafeteria benefits for the employees to choose, perform benchmarking with other organisations to adapt best practices and encourage the Water Cooler culture which allows SME owners to gain insightful feedback from their employees.